2013
DOI: 10.1186/1472-6963-13-184
|View full text |Cite
|
Sign up to set email alerts
|

Adult ADHD patient experiences of impairment, service provision and clinical management in England: a qualitative study

Abstract: BackgroundThere is limited evidence of the unmet needs and experiences of adults with Attention Deficit Hyperactivity Disorder (ADHD) in the published scientific literature. This study aimed to explore the experiences of adults in England with ADHD regarding access to diagnostic and treatment services, ADHD-related impairment and to compare experiences between patients diagnosed during adulthood and childhood.MethodsIn this qualitative study, 30 adults with ADHD were recruited through an ADHD charity (n = 17) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
125
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(132 citation statements)
references
References 38 publications
5
125
1
Order By: Relevance
“…Neglecting or being denied help by healthcare professionals was perceived to generate the pain of both increased anxiety and feelings of disappointment, which escalated into physical pain. As the results of other studies have shown, interviewees have stated that much of their suffering could have been avoided if they had received the diagnosis earlier [30] [31] [32]. The findings confirm that suffering can prompt feelings of alienation, both from others and from oneself.…”
Section: Discussionsupporting
confidence: 74%
“…Neglecting or being denied help by healthcare professionals was perceived to generate the pain of both increased anxiety and feelings of disappointment, which escalated into physical pain. As the results of other studies have shown, interviewees have stated that much of their suffering could have been avoided if they had received the diagnosis earlier [30] [31] [32]. The findings confirm that suffering can prompt feelings of alienation, both from others and from oneself.…”
Section: Discussionsupporting
confidence: 74%
“…The wishes of patients ''to be listened to non-judgmentally'' and ''to pay attention to the possible change in needs'' are also described in a study of Billsborough et al (2014) on support needs during periods of mania and depression for people with bipolar disorder. The desire of adults with ADHD for more accessible and continuous care, which includes treatments not typically offered for ADHD, have also been described in the UK in a study on patients' experiences of impairment, service provision and clinical management (Matheson et al, 2013). The importance, as well as the potential problems, of a health professional acting professionally and demonstrating empathy as a person is also described by a study of Eliacin et al (2015) on the patients' understanding of shared decision making in mental health setting and Williams et al (1999) on the user perspectives on person-centeredness in social psychiatry.…”
Section: Discussionmentioning
confidence: 99%
“…Broad variation of services was also captured in this study, ranging from health care providers and special education interventions to labour employment and social security programs. Despite the extensive impact of ADHD on individual functioning, there is still a growing demand for services that can be offered in addition to pharmacological treatments [56]. The need for non-pharmacological interventions can be explained by numerous reasons.…”
Section: Identified Icf-cy Categoriesmentioning
confidence: 99%